Representation of Social Class in The Outsiders by S.E. Hinton Novel - Amiin, Ihsanul; Zamruddin, Mardliya Pratiwi; Sudirman, Eka Pratiwi (Fakultas Ilmu Budaya Universitas Mulawarman, 2025)
This research is concerned with the representation of bourgeoisie and proletariat social class in The Outsiders by S.E. Hinton novel. This research aimed to describe the Socs and the Greasers. This research used a characterization; direct and indirect to find representation of bourgeoisie and proletariat social class characteristic. This research used a qualitative research design with a descriptive method. The data in this research were quotations, narrations, words, phrases, clauses, sentences, or paragraphs that are related to buorgeoisie and proletariat social class characteristic and obtained by reading the novel. In the analysis, the researcher used Marxist theory. The result showed that the Socs represent the bourgeoisie and the Greasers represent the proletariat. The Socs has five bourgeoisie social class characteristic; ownership of capital, control of the means of production, wealth, education, and culture. While the Greasers has five proletariat social class characteristic; working class, low income, exploited, lack of education, and sense of solidarity. The researcher found that the Socs as bourgeoisie and the greasers as proletariat.